Idaho Explosives Detection System: Development and Enhancements - Reber, Edward L.; Blackwood, Larry G.; Edwards, Andrew J.; Egger, Ann E.; Petersen, Paul J. (Sensing and imaging, 2007)
The Idaho Explosives Detection System (IEDS) was developed at the Idaho National Laboratory (INL) to respond to threats imposed by delivery trucks carrying bulk explosives into military bases. The system consists of two platforms, one on each side of a subject vehicle. Each platform includes a neutron generator and an array of sodium iodide (NaI) detectors. The two neutron generators are pulsed and synchronized. A computer connects to the system via Ethernet and is able to control the system remotely. The system was developed to detect bulk explosives in a medium size truck within a 5-min measurement time. In 2004, a full-scale prototype IEDS was built for testing and continued development. System performance was successfully tested at the INL from November 2005 to February 2006 using different types of real explosives with a variety of cargo. Recently, the first deployable prototype system was installed at Wright-Patterson Air Force Base in Ohio and has been in operation since May 2007. The capability of passively detecting radiological material within a delivery truck has also been added.